Rapid Manufacturing of Mechanoreceptive Skins for Slip Detection in Robotic Grasping. Issue 1 (11th November 2016) - Charalambides, Alexi; Bergbreiter, Sarah
Abstract : A simple and rapid method to manufacture all‐elastomer robot skins with normal and shear force sensing is presented. The milling‐based approach creates reusable molds with microscale features over a large area, and the tactile sensors can operate via contact resistance or capacitance. A contact resistance sensor is incorporated into a 1 degree‐of‐freedom robotic gripper for closed‐loop slip detection.